Catalytic upgrading of citric acid to environmental friendly tri-butyl citrate plasticizer over ultra stable phosphonated Y zeolite - Nandiwale, Kakasaheb Y.; Gogoi, Pranjal; Bokade, Vijay V. (Chemical Engineering Research & Design, 2015)
The catalytic synthesis of non-toxic/eco-friendly tributyl citrate (TBC) plasticizer by esterification of renewable citric acid (CA) with butanol would be completely sustainable route. In this context, catalytic performance of parent ultra stable Y (USY) and phosphonated USY catalysts were investigated for TBC synthesis. Parent USY and phosphonated USY catalysts were characterized by powder X-ray diffraction (XRD), N-2 adsorption-desorption, NH3 temperature programmed desorption (TPD), pyridine-Fourier Transform Infrared Spectroscopy (FTIR), FTIR, SEM, ICP. The influence of various process parameters such as phosphorous (P) loading (0 to 4 wt/%), catalyst loading (5-25%), molar ratio of CA to n-butanol (1:4 to 1:12), reaction temperature (383-423 K) and reaction time (1-5 h) have been investigated over USY catalyst with aim to maximize CA conversion and TBC yield. Amongst the studied catalysts, the 2% (w/w) P/USY was found to be highly potential catalyst with complete CA conversion (100%) and 93% TBC yield. The present method of using 2% (w/w) P/USY catalyst for the synthesis of TBC would be environmentally benign in the context of bio-renewable synthetic route, high catalytic activity, non-toxic product, long term stability and reusability of catalyst (five catalytic cycles). (c) 2015 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved,
Keywords: Butanol; Citric acid; heterogeneous catalysis; Plasticizer; Tributyl citrate

Controlling and stabilization of Ru nanoparticles by tuning the nitrogen content of the support for enhanced H-2 production through aqueous-phase reforming of glycerol - Gogoi, Pranjal; Kanna, Narsimharao; Begum, Pakiza; Deka, Ramesh C.; Satyanarayana, C. V. V.; Raja, Thirumalaiswamy (ACS Catalysis, 2020)
The stable activity of catalysts is an important issue in catalysis, particularly aqueous-phase reforming (APR) of renewable oxygenates, of biomass origin, to get H-2. Sintering of metal nanoparticles on supports affects catalyst stability. To alleviate this problem, a series of highly stable Ru-supported catalysts with controlled metal nanoparticle sizes have been prepared via the easy incipient wetness impregnation method. These catalysts were used for APR of glycerol to produce H-2. Nitrogen-doped mesoporous carbons (NMCs) were utlized as supports and found to have a strong influence on the catalytic performance of the catalysts. Incorporation of nitrogen in the carbon framework significantly enhanced the catalytic activity compared to Ru catalysts on nitrogen-free supports. Notably, the catalyst (5 wt % Ru-NMC-3) with optimal N content (10.9 wt %) demonstrated improved stability and H-2 selectivity, which are better than those of many state-of-the-art catalysts. Nitrogen in the carbon framework has a dual relationship with the activity of the catalyst: (i) it creates basic environment over the catalysts support and (ii) it acts as an anchoring site for metal nanoparticles. Anchoring of metal nanoparticles has helped to curb their sintering, thus leading to better stability of the catalysts under APR reaction conditions. Various characterization techniques were employed to understand the nature of active catalytic sites responsible for higher H-2 production while minimizing CO formation. In situ CO-FTIR studies showed that the higher catalytic activity of 5 wt % Ru-NMC-3 catalyst was attributed to the enhanced WGS activity over this catalyst. Density functional theory calculations were performed to understand the stabilization of metal nanoparticles by different types of N present on the support and provide insights into the prefered sites of glycerol adsorption on the NMC support. Since S wt % Ru-NMC-3 was the relatively best catalyst, it was selected for the preparation of bimetallic catalysts. Accordingly, addition of Pt to this system helped to increase the stability of the catalyst. This bimetallic catalyst may, therefore, find application for wide use in APR of biomass oxygenates.
Keywords: aqueous-phase reforming; Glycerol; H-2 production; Ru/NMC catalyst; synergistic effect